Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/polym14030602
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Biomimetically Mineralized Collagen Scaffolds on Bone Cell Proliferation and Immune Activation

Abstract: Collagen, as the main component of connective tissue, is frequently used in various tissue engineering applications. In this study, porous sponge-like collagen scaffolds were prepared by freeze-drying and were then mineralized in a simulated body fluid. The mechanical stability was similar in both types of scaffolds, but the mineralized scaffolds (MCS) contained significantly more calcium, magnesium and phosphorus than the unmineralized scaffolds (UCS). Although the MCS contained a lower percentage (~32.5%) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 83 publications
(149 reference statements)
0
10
0
Order By: Relevance
“…The reduction and disorganization of type I collagen might not only change the structure, but also affect the function of the heart ( 10 ). OI is a complex disease in which the quantity or the structure of collagen could be changed, therefore, hearts and main pulmonary arteries might be involved in OI patients ( 5 ). A previous study revealed that the heart and main pulmonary artery had decreased numbers and disorganization of collagens in perinatal lethal OI type II patients ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The reduction and disorganization of type I collagen might not only change the structure, but also affect the function of the heart ( 10 ). OI is a complex disease in which the quantity or the structure of collagen could be changed, therefore, hearts and main pulmonary arteries might be involved in OI patients ( 5 ). A previous study revealed that the heart and main pulmonary artery had decreased numbers and disorganization of collagens in perinatal lethal OI type II patients ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in Oim mouse model with defects of α2 chains of type I collagen, a disturbance in the ascending aorta was found, but without significant changes in LV structures and functions ( 36 , 37 ). As type I collagen is a heterotrimer of two α1 and one α2 chains ( 5 ), we speculated that the difference of echocardiographic abnormalities might be correlated to the different changes in the structure and metabolism of type I collagen induced by various pathogenic gene mutations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies reported that collagen scaffolds combined with HAp improved bone formation, because they were readily absorbed. Likewise, studies demonstrated that collagen scaffolds, despite having mechanical properties similar to those of other scaffolds, when combined with HAp and other minerals improved cell proliferation by means of osteogenic and osteoimmunomodulation processes [ 26 , 27 , 28 , 29 ]. Hence, the aim of the present study was to investigate the possible beneficial effects of HAp-egg shell collagen scaffolds enriched with PLGA/PRF for PdLF cell adhesion and viability.…”
Section: Introductionmentioning
confidence: 99%